Localization results for the Lagrange max-product interpolation operator based on equidistant knots - Coroianu, Lucian; Gal, Sorin G. (Rev. Anal. Numér. Théor. Approx., 2013)
In the class of strictly positive functions strong localization results are obtained in approximation by the Lagrange max-product interpolation operators based on equidistant nodes. The results allow to approximate locally bounded strictly positive functions with very good accuracy. Then, it is observed that the results can be extended to bounded functions of variable sign.